Economic losses experienced by smallscale farmers in Malawi due to cassava brown streak virus disease - Gondwe, F.M.T.; Mahungu, N.M.; Hillocks, R.J.; Raya, M.D.; Moyo, C.C.; Soko, M.M.; Chipungu, Felistus P.; Benesi, I.R.M. (2003)
Cassava is an important root crop in Malawi. It is the second most important food crop after maize. It is grown throughout the country as a food security crop, sack/cash crop, and as a staple food crop along the Lake Malawi. Is is a staple for over 39 % of the country’s population. Farmers are not benefiting as much as they might from cassava because they are faced with a number of constraints. These include: - inherent low yielding and late maturing local cultivars - pests and diseases prevalent in the country - low promotion of good cultural practices. The major pests and diseases of cassava in Malawi are, cassava mosaic virus disease (CMD), cassava bacterial blight (CBB), cassava brown streak virus disease (CBSD), cassava green mite (CGM), cassava mealy bug (CM) and termites. The objective of this study was to determine the economic impact of CBSD on the farmers in Malawi where the disease is prevalent. The paper makes the following recommendations: - the cassava research organisations should mount urgent awareness campaigns of the disease and its management for both extension agents and farmers - the cassava research organisations should establish effective collaboration with the extension system on matters of proper cassava husbandry to effectively and efficiently control the disease - they should additionally carry out local collection exercises for cultivars that show CBSD disease resistance in the high disease pressure areas - there is an urgent need for cassava research and extension organisations to multiply cultivars and promising clones that have shown multiple disease resistance and that are widely accepted by farmers for distribution in the heavily affected areas - in collaboration with entrepreneurs, these organisations need to develop and strengthen sustainable seed multiplication and distribution systems as a way of assuring the provision of clean planting material.